Transformative Education: The Catalyst for Change in Sub-Saharan Africa - Claretah, Makuvire; Pinias, Chikuvadze; Mudavanhu, Young; Dziva, Daimond (Quality Assurance Practices for Transformative Higher Education in Southern Africa, 2025)
Sub-Saharan Africa operates in an increasingly complicated and linked environment. Global issues like climate change collide with local biodiversity loss. Growing global inequality combines with local social disparities, economic problems, the normalisation of violence, and a decline in mental health and socioemotional resilience at the individual and community levels. Education has the potential to positively influence individuals and communities. Education may also be a significant tool for promoting equality for marginalised groups, as well as a catalyst for progress. The chapter delves into transformative education, as defined in SGD 4.7, and its ability to bring about change in SSA.